The Promotion of the Participatory Learning in Marketing Demonstrative Center Administration of Kham Phai Village Mueang District Kalasin / การส่งเสริมการเรียนรู้แบบมีส่วนร่วมในการบริหารจัดการศูนย์สาธิตการตลาดชุมชนบ้านคำไผ่ อำเภอเมือง จังหวัดกาฬสินธุ์ - Ampasri Phokha and Peerapot Nitipot / สุกัญญา ดวงอุปมา อำภาศรี พ่อค้า และพีรพจน์ นิติพจน์, Sukanya Duanguppama, (Journal of Community Development Research (Humanities and Social Sciences), 2016)
บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาสภาพการจัดการศูนย์สาธิตการตลาดและการมีส่วนร่วมของคนในชุมชนกระบวนการวิเคราะห์สายโซ่อุปทาน และกระบวนการจัดการความรู้ของศูนย์สาธิตการตลาดและนำองค์ความรู้ที่เป็นเลิศมาถ่ายทอดแก่กลุ่มเพื่อสร้างความเข้มแข็ง เกิดกระบวนการมีส่วนร่วม สร้างความสามัคคีของคนในชุมชน การวิจัยนี้เป็นวิจัยที่มีกระบวนการวิจัยแบบเทคนิคการวิจัยเชิงปฏิบัติการโดยประชาชนมีส่วนร่วม (PAR) เน้นระเบียบวิธีวิจัยเชิงคุณภาพ โดยมาจากคณะกรรมการ สมาชิก และคนในชุมชนเป็นผู้มีส่วนร่วมในการบริหารจัดการศูนย์สาธิตการตลาด โดยมีขอบเขตการศึกษา คือ ศูนย์สาธิตการตลาดบ้านคำไผ่ อำเภอเมือง จังหวัดกาฬสินธุ์ พบว่า บริบทศูนย์สาธิตศูนย์สาธิตการตลาดบ้านคำไผ่ มีการบริหารจัดการศูนย์สาธิตการตลาดในรูปแบบของคณะกรรมการ มีจำนวนสมาชิก 115 ครัวเรือน มีการแบ่งเงินปันผลให้กับคณะกรรมการศูนย์สาธิต บำรุงศูนย์สาธิตการตลาด และค่าตอบแทนหุ้น นำเสนอขายสินค้าให้กับคนในชุมชนในราคา ที่เหมาะสมและมีการส่งเสริมการเรียนรู้แบบมีส่วนร่วมในการบริหารจัดการ การสร้างความตระหนักและเห็นคุณค่าร่วมแก้ไขปัญหาในการบริหารจัดการศูนย์สาธิตการตลาดอย่างมีส่วนร่วม เกิดการวิเคราะห์สายโซ่อุปทาน ด้านการจัดการและการตลาด ตลอดจนมีการถ่ายทอด องค์ความรู้ด้านการบริหารจัดการศูนย์สาธิตการตลาด การร่วมแลกเปลี่ยนเรียนรู้เทคนิคการบริหารจัดการสมัยใหม่เพื่อใช้ในการบริหารจัดการศูนย์สาธิตการตลาด เพื่อเป็นแนวทางในการพัฒนาศูนย์สาธิตการตลาดให้เกิดการพัฒนาที่ยั่งยืนต่อไป   คำสำคัญ: การบริหารจัดการ  ศูนย์สาธิตการตลาด  การเรียนรู้แบบมีส่วนร่วม   สายโซ่อุปทาน  การจัดการความรู้   Abstract This study aimed at studying the status of Marketing Demonstrative Center administration and the participation of the people in community, the supply chain, and the process of knowledge management of the Marketing Demonstrative Center and the adaptation of knowledge to the group to build up the strength in terms of participation and unity of the people in community. This study employed the participatory action research (PAR) technique through the qualitative method. The data were obtained from the community committees, members of community, and the people in community who have the participation in administration of the Marketing Demonstrative Center. The scope of this study was Kham Phai village, Mueang district, Kalasin province. The results revealed that the Kham Phai village Marketing Demonstrative Center was administered under the committees. The members were 115 households. The dividend was divided to the committees of the demonstrative center, the demonstrative center, and for the members. The goods were sold to the people in community in a reasonable price. There were the promotions on participatory learning in administration, awareness development and participation in solving problem in administration, and the analysis of supply chain on management and marketing. There were also be the knowledge transfer on Marketing Demonstrative Center administration and the sharing on modern techniques for Marketing Demonstrative Center administration for being the approach for the sustainable development of the Marketing Demonstrative Center.     Keywords : Administration, Marketing Demonstrative Center, Participatory Learning, Supply Chain, Knowledge Management
Keywords: การบริหารจัดการ ศูนย์สาธิตการตลาด การเรียนรู้แบบมีส่วนร่วม สายโซ่อุปทาน การจัดการความรู้ Administration, Marketing Demonstrative Center, Participatory Learning, Supply Chain, Knowledge Management